ORNAC in a Nutshell - Balcom, Corina (Operating Room Nurses Association of Canada Journal, 1997)
The Board and Executive of the Operating Room Nurses Association of Canada met in Ottawa, April 26 & 27, 1997. The meeting was attended by five Executive and twenty Board members. Following are highlights of the meeting: